Introduction to 1st Issue of AJDHM - ASEAN Journal of Disaster Health Management (Universitas Gadjah Mada, 2025)
The ASEAN Journal of Disaster Health Management (AJDHM) is proud to announce the successful release of its inaugural issue, now available online as of January 2, 2025. This milestone marks a significant step forward in our mission to advance research and collaboration in the field of Disaster Health Management.